Peran Pengembangan Karier, Kepemimpinan Humanis, Integritas Profesi, dan Manajemen Kinerja terhadap Modernisasi SDM Polri - Riyadi, Slamet; Lubis, Rahmadsyah (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to analyze the role of career development, humanistic leadership, professional integrity, and performance management in the modernization of human resources within the Indonesian National Police (Polri). HR modernization is a crucial component of police reform, encompassing competency enhancement, professionalism, and adaptation to technological changes and societal demands. The study uses a literature review method, reviewing 50 scholarly articles, national and international journals, and official Polri reports from the last ten years (2015–2025). Findings indicate that systematic career development increases capacity and motivation, humanistic leadership fosters an inclusive and supportive work culture, professional integrity strengthens ethics and compliance, while performance management ensures objective and continuous evaluation. The integration of these four factors significantly contributes to HR modernization, enhancing public service quality, operational efficiency, and technological adaptation. The literature emphasizes career planning based on competency, application of humanistic leadership in team management, strengthening integrity through codes of conduct and training, and transparent performance management systems. These findings provide a foundation for Polri policymakers to design effective, sustainable, and adaptive HR modernization strategies in response to social and technological dynamics.